2009
DOI: 10.1192/bjp.bp.108.055376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age at onset of schizophrenia on white matter abnormalities

Abstract: White matter abnormalities in frontal regions in schizophrenia may depend on developmental stage at the time of illness onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
64
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 43 publications
(65 reference statements)
12
64
3
1
Order By: Relevance
“…We found lower fractional anisotropy in our first-episode psychosis group than in the control group in the genu of the corpus callosum and in the right minor forceps (as reported by Perez-Iglesias and colleagues 16 ), in the right superior longitudinal fasciculus and the right corticospinal tract (as reported by Kyriakopoulos and colleagues 17 ), and in the left middle cerebellar peduncle (as reported by Kyriakopoulos and colleagues 19 ). Compared to ROI studies, our findings are congruent with the lower fractional anisotropy reported in the genu of the corpus callosum, right superior longitudinal fasciculus and left inferior longitudinal fasciculus in patients with first-episode psychosis.…”
Section: White Matter Changes In First-episode Psychosissupporting
confidence: 85%
See 2 more Smart Citations
“…We found lower fractional anisotropy in our first-episode psychosis group than in the control group in the genu of the corpus callosum and in the right minor forceps (as reported by Perez-Iglesias and colleagues 16 ), in the right superior longitudinal fasciculus and the right corticospinal tract (as reported by Kyriakopoulos and colleagues 17 ), and in the left middle cerebellar peduncle (as reported by Kyriakopoulos and colleagues 19 ). Compared to ROI studies, our findings are congruent with the lower fractional anisotropy reported in the genu of the corpus callosum, right superior longitudinal fasciculus and left inferior longitudinal fasciculus in patients with first-episode psychosis.…”
Section: White Matter Changes In First-episode Psychosissupporting
confidence: 85%
“…The voxel-based analysis (VBA) indicated a lower fractional anisotropy in patients than in controls that concerned both the interhemispheric tracts of the corpus collosum and long intrahemispheric tracts, such as the superior and inferior longitudinal fasciculus and inferior occipitofrontal fasciculus. 16,17 Other areas of lower fractional anisotropy included the uncinate fasciculus, cingulum bundle, anter ior thalamic radiation, corticospinal tract and cerebellum projections. [16][17][18][19] Similarly, ROI studies reported a lower fractional anisotropy in the corpus callosum, uncinate fasciculus, superior longitudinal fasciculus and inferior longitudinal fasciculus in patients with first-episode psychosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,12,[20][21][22] Previous studies assessing the effect of age at FEP on brain structure suggest that earlier onset is associated with greater disruption of structural brain development. 7,[23][24][25][26] However, interpretation of these results may be hampered by using age as a linear variable and disregarding the nonlinear relationship of age with brain development, 24,26 stratifying cases into several onset (adolescent/adult) groups instead of treating age as a continuous variable, 23,25 and using a narrow age-range sample of patients which does not encompass important stages of brain development. 7 We do not know of a study assessing the nonlinear effect of age on brain deficits in FEP patients whose first-episode onset ranges from early adolescence through adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that whereas low levels of neonatal corticosterone improved adult cognitive abilities and increased na-Abs levels directed to SERT, high doses of neonatal corticosterone-reduced hippocampal BDNF levels and na-Abs directed to DAT, confirming the notion that both adaptive plasticity and pathological outcomes in adulthood may depend on circulating neonatal corticosterone levels and that these effects follow a U-shaped profile. The notion of resilience, as contributed by gene-environment interactive factors, on predisposition and disease expression in affective disorder states, such as bipolar disorder, has accumulated increasing status in the consideration of developmental contributions (Alsuwaidan et al 2009;Feder et al 2009;Frangou 2009;Katz et al 2009;Kempton et al 2009;New et al 2009). …”
Section: Neurodevelopmental Staging In Affectmentioning
confidence: 99%